Using Peer Tutoring To Enhance Pre-Service Teachers Performance In Physics. - Osei-Himah, Valentina (International Journal of Scientific Research and Management (IJSRM), 2021)
The study used peer tutoring to teach pre-service teachers to improve their performance in physics at Atebubu College of Education in Ghana. To achieve the purpose of the study an action research design was used.  A total number of 140 were purposively selected. Quantitative data was collected from pre-service teachers using achievement test and questionnaire as the main research instruments. Through the analysis of the quantitative data using percentages, means, standard deviation, it was found that the pre-service teachers’ performance in physics was enhanced as a result of the peer tutoring method adopted for the study. It was recommended that, Science tutors at the Colleges of Education are encouraged to adapt to the teaching and learning of scientific concepts through peer tutoring means as the findings of the study has shown that peer tutoring teaching and learning of physics help reduce students’ forgetfulness and recitation of scientific concepts.